DRP MODEL: importance of logistics as a distribution strategy in a food company - Costa Alexandre, Tarik; Marcela Midori Yada de Almeida (Revista Interface Tecnológica, 2022)
In the current market of extreme competition, logistics plays a vital role, gaining new markets for companies, undergoing adaptations in their production processes so that they could meet new customer requirements, the arrival of new competitors and consumers, greater awareness of society, of the business world. In this context, logistics is indispensable, being understood as the management of the flow of materials and information from their point of acquisition to their point of consumption. There is also a concern with the reverse logistical flow, which goes from the point of consumption to the point of origin, and which needs to be managed. Thus, efficiency in transport and stock management is of great importance for competitive advantage, the objective of this paper is to present a DRP (Distribution Planning) tool being used for stock management of a food company, more specifically tomato sauce. The work leads to the continuation of similar studies, as it is a current theme in any field of activity of organizations and of high complexity and need, always in search of improved distribution and cost reduction, means of management tools. Thus, this article does not seek to close the discussion on the topic, but rather to contribute to understanding
Keywords: DRP; Business management; Logistics